Pengaruh Gaya Kepemimpinan dan Loyalitas Kerja terhadap Kinerja Pegawai pada Kantor Satuan Polisi Pamong Praja dan Pemadam Kebakaran Kabupaten Sikka - Faustina Peni Hayon; Imanuel Wellem; Viktor Eko Transilvanus; Kristina Sujila (Journal Economic Excellence Ibnu Sina, 2024)
The background of this research is the low level of employee performance in the Civil Service Police Unit and the Sikka Regency Fire Department. This research aims to: (1) determine the description of employee performance, leadership and work loyalty; (2) analyze the influence of Leadership and Work Loyalty on employee performance both partially and simultaneously. The population in this study were employees of the Sikka Regency Civil Service Police Unit and Fire Department, totaling 94 people. Because the population is limited, this research was conducted by census or saturated sampling. Data was collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is carried out through the F test and t test. The results of the descriptive analysis show that the background to the employee performance variable is in good criteria, the Leadership variable is in good criteria, then the Work Loyalty variable is in good criteria. The statistical results of the t test show that partially the Leadership variable has a positive and significant effect on employee performance. Furthermore, the Work Loyalty variable has a positive and significant effect on employee performance. The statistical results of the F test show that simultaneously the Leadership and Work Loyalty variables have a significant effect on employee performance. The results of the determination analysis show that the two independent variables in this study are able to explain variations in the ups and downs in performance of employees at the Civil Service Police Unit and the Sikka Regency Fire Department by 31%.